Hip Fracture Risk Assessment and Reduction: An Interdisciplinary Approach. Issue 2 (April 2018) - Hull, Jonathan
Abstract : The prevalence of hip fractures continues to rise exponentially, and is directly related to the aging population. Patients with hip fracture continue to have increased 30-day and 1-year mortality rates. The postinjury morbidity and mortality rates are well-documented. With this morbidity and mortality, health-care expenditures continue to increase and negatively impact society. The health-care industry must continue to innovate and perform research to reduce morbidity and mortality rates in patients with hip fracture. A detailed literature review was conducted to research methods to help reduce morbidity and mortality related to hip fracture.